Utilização de aula demonstrativa como modalidade didática no ensino/aprendizagem em estudo de fisiologia vegetal - Nascimento, Lilian Loren dos Anjos Muniz do (Brasil, 2022)
The teaching of Biology, Botany is one of the areas that present the biggest difficulty in terms of assimilating contents by the student, respected because of exhaustion and monotonous, and has become a challenge for teachers who have to seek diverse ways to contextualize the contents in order to attract and attract attention of these students. In this context, this research aimed at the use of demonstrative class as a didactic modality for the students' approach to the plant kingdom and the phytoremediation technique, which was carried out during the supervised curriculum internship III and IV, developed in IFAM Federal Institute of Education, Science and Technology of Amazonas, Campus Manaus - Centre in the classes of the 2 year of high school integrated to the technician of information technology, mechanics, buildings and chemistry. A total of 157 male and female students aged 15 to 20 years. The methodology employed was qualitative in nature. A questionnaire was used as a data collection instrument, field notebook and participant observation. After the application of the previous questionnaire, the content proposed in our research with an expository class dialogue was started contextualizing the importance of plants in the daily life, mechanisms of absorption and conduction of substance by the plant and phytoremediation, Later, a demonstrative lecture on the conduction of substances by plants. At the end of the activities and as an evaluation students were asked to write a text using the botanical terms used during the classes and the application of an evaluation questionnaire. Among the results obtained with our research we realized that the students still had knowledge about phytoremediation technique and were very participative both in the demonstrative class and participation in the questionnaires.